Methods of legislation convergence of states: experience of the European Union (International relations and international law Journal, 2016)
This article is devoted to the practice of unification and harmonization of the national legislation of the member States of the European Economic Community, the European Union. The author paid special attention to the various legal methods of harmonization. In particular, the analysis of methods of legal convergence, such as the «final» method, «the circular» method and «reference» method. In addition, emphasized the value in the implementation of the unification of regulations, directives and decisions of the EU and EC. As an example, considers the Directive adopted by the European community and the European Union.
Keywords: unification; harmonization; member States; the European Union; the Council of the European communities; the European Parliament; the regulations; directive